2015
DOI: 10.1113/jphysiol.2014.283549
|View full text |Cite
|
Sign up to set email alerts
|

Muscle microvascular blood flow responses in insulin resistance and ageing

Abstract: Insulin resistance plays a key role in the development of type 2 diabetes. Skeletal muscle is the major storage site for glucose following a meal and as such has a key role in maintenance of blood glucose concentrations. Insulin resistance is characterised by impaired insulin-mediated glucose disposal in skeletal muscle. Multiple mechanisms can contribute to development of muscle insulin resistance and our research has demonstrated an important role for loss of microvascular function within skeletal muscle. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
83
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(86 citation statements)
references
References 65 publications
(146 reference statements)
3
83
0
Order By: Relevance
“…Similar results were obtained for metabolic syndrome and type-2-diabetes as age-related conditions [3539], supporting a novel ‘vascular paradigm’ of insulin resistance, i.e. an attenuation of insulin-mediated recruitment of capillary exchange surface and transendothelial insulin transport as rate limiting steps for insulin (and glucose) delivery to skeletal muscle [36, 3945]. Regarding exercise-induced microvascular response, human studies are limited to patients with diabetic microangiopathy [46].…”
Section: Introductionsupporting
confidence: 83%
“…Similar results were obtained for metabolic syndrome and type-2-diabetes as age-related conditions [3539], supporting a novel ‘vascular paradigm’ of insulin resistance, i.e. an attenuation of insulin-mediated recruitment of capillary exchange surface and transendothelial insulin transport as rate limiting steps for insulin (and glucose) delivery to skeletal muscle [36, 3945]. Regarding exercise-induced microvascular response, human studies are limited to patients with diabetic microangiopathy [46].…”
Section: Introductionsupporting
confidence: 83%
“…) and humans (reviewed by Keske et al . , in this issue). These increases are important, as they are part of the redistribution of the fuels that are absorbed with each of the main meals and therefore play an important role in the delivery of glucose, insulin and fatty acids to skeletal muscle as the main storage site.…”
Section: Introductionmentioning
confidence: 81%
“… and Keske et al . ). This suggests that the postprandial redistribution of the blood flow to skeletal muscle and potentially subcutaneous adipose tissue is reduced or absent in obese, elderly and insulin‐resistant individuals.…”
Section: Introductionmentioning
confidence: 97%
“…Reductions in vascular function in response to aging and/or diabetes may be due in part to reductions in NO synthesis and a reduced NO-mediated vasodilatory response to feeding-induced hyperinsulinemia (24). Consequently, a reduction in NO-mediated vascular function may attenuate postprandial plasma amino acid delivery to tissues, thereby having a negative impact on normal feeding-mediated increases in postprandial muscle protein synthesis rates.…”
Section: Discussionmentioning
confidence: 99%
“…However, aging and insulin resistance are associated with reduced skeletal muscle capillary density, impaired endothelial function, and reduced nitric oxide (NO) availability (14,20,32,39,40). As such, age-related impairments in vascular function due to an impaired NO-mediated vasodilatory response and decreased muscle tissue perfusion may diminish feeding-mediated increases in muscle protein synthesis and, thus, contribute to the anabolic resistance of aging (7,24).It has been reported that dietary nitrate (NO 3 Ϫ ) supplementation, via sequential reduction of NO 3 Ϫ to nitrite (NO 2 Ϫ ) and NO, can stimulate NO synthesis and increase NO bioavailability (55). Moreover, it has been suggested that NO has a role in promoting insulin delivery to skeletal muscle tissue and increasing insulin-stimulated muscle perfusion and capillary action (22, 51).…”
mentioning
confidence: 99%